Analisis Manajemen Risiko Berdasarkan ISO 31000 Pada Pesantren Luhur Al- Husna Wonocolo Surabaya - Feby Fitriani Sudarsono; Randa Wahyu Saputra; Nabila Sani; Nurul Fariidhotun Nisa; Iftakhul Jannah; Indri Sudawati Rozas (UNIVERSITAS PGRI MADIUN, 2020)
Pesantren Luhur Al-Husna is a boarding school that accepts students as a santri. The pesantren, which was established in 2003, is located at Jemur Wonosari Gang Masjid No.42, Jemur Wonosari, Wonocolo District, Surabaya, East Java. Pesantren Luhur Al-Husna has a students around 200. In this pesantren there are often problems in operational management. One of the problems that often occur in this pesantren is the frequent occurrence of loss of goods and damage to existing facilities in the cottage. So this study has the aim of recommending risk management at the Pesantren Luhur Al-Husna Wonocolo Surabaya. In this study using qualitative methods by conducting interviews and observations. Therefore as a basis for this research using ISO 31000 becomes the basis for the application of risk management. In risk management which consists of identifying risks, analyzing risks, evaluating risks and treating risks. In this study 9 risks were identified such as administrative risk, loss of goods, and data management. And categorized into several indexes, namely extreme, high, medium, and low.Keywords: Risk Management, Pesantren Luhur Al-Husna Wonocolo Surabaya,, ISO 31000, Qualitative method, Index